State of the Art of Intraoperative Ultrasound in Liver Surgery: Current Use for Staging and Resection Guidance - Donadon, M.; Costa, G.; Torzilli, G. (Ultraschall in der Medizin - European Journal of Ultrasound, 2014)
The performance of hepatic surgery without a parenchyma-sparing strategy carries significant risks for patient survival because of the not negligible occurrence of postoperative liver failure. In modern liver surgery the use of intraoperative ultrasound (IOUS) includes staging of the liver disease and more importantly resection guidance. IOUS allows the performance of so-called “radical but conservative surgery”, which is pivotal in offering a chance of a cure to an increasing number of patients who until a few years ago were considered only for palliative care. The present article details the rationale of IOUS for staging and for resection guidance in liver surgery.